Argentina, waterfront buildings and church on Beagle Channel in Ushuaia - Forman, Harrison, 1904-1978 (1954)
Ushuaia - Southernmost town in the world at stinger-tip of S. [South] America (Argentina). It is 60 mi. from Cape Horn, 450 mi. from Antarctica. Color Box 7